2003
DOI: 10.1023/b:jadd.0000006001.00667.4c
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability in Children with Autism Spectrum Disorder

Abstract: Maintaining upright posture is a complex process involving multiple afferent systems. The aim of this study was to measure the postural stability of children with Autism Spectrum Disorder (ASD) compared with children with typical neurodevelopment and to measure the relative contributions of the visual, somatosensory, and vestibular afferent systems in each group. Eight boys with ASD and eight age-, race-, and gender-matched controls participated in this study using force platform technology with customized sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
170
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(192 citation statements)
references
References 36 publications
15
170
1
6
Order By: Relevance
“…The groups reacted differently to the removal of vision: for the range of the COP in the ML direction, the destabilizing effect of closing the eyes was larger for the ASD group than for controls. This finding is consistent with earlier studies [8,23], and suggests that individuals with ASD have greater reliance on visual input for the regulation of balance, making it more difficult to maintain balance with the eyes closed. A recent study [28] revealed unexpected and substantial superiority in visual motion perception in children with ASD, compared to controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The groups reacted differently to the removal of vision: for the range of the COP in the ML direction, the destabilizing effect of closing the eyes was larger for the ASD group than for controls. This finding is consistent with earlier studies [8,23], and suggests that individuals with ASD have greater reliance on visual input for the regulation of balance, making it more difficult to maintain balance with the eyes closed. A recent study [28] revealed unexpected and substantial superiority in visual motion perception in children with ASD, compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies [8,23] have found decreased postural performance in ASD when the eyes are closed. Closing the eyes leads to a shift toward other sensory modalities to regulate balance, necessitating more attentiondemanding control of balance.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…These speak of deficits such as in handwriting (Kushki, Chau, & Anagnostou, 2011) and (relatedly) fine-precision grip (David, Baranek, Wiesen, Miao, & Thorpe, 2012); in postural stability (Molloy, Dietrich, & Bhattacharya, 2003) and as documented in the studies above, gait (Esposito & Venuti, 2008;VernazzaMartin et al, 2005;Vilensky, Damasio, & Maurer, 1981); of akinesia, dyskinesia and bradykinesia (Damasio & Maurer,6 Motor symptoms are not the only symptoms that appear in the first year of life; we refer the interested reader to several other papers which point out early abnormalities in social orientation among other symptoms in the first year of life (Clifford & Dissanayake, 2008;Clifford et al, 2013;Clifford, Young, & Williamson, 2007;Dawson et al, 2004;Maestro, Muratori, Barbieri et al, 2001; 1978; Maurer & Damasio, 1982); and finally of hand dystonia and facial grimacing (Wing, 1981).…”
mentioning
confidence: 99%
“…This finding was attributed to a sensory integration impairment reflected in hypo-reactivity to visual sway-inducing information. In the proprioceptive domain, Molloy et al (2003) asked TD and ASD children to stand on a fixed surface and on foam with and without vision. They showed that children with ASD exhibited greater sway areas, with this effect increasing with task difficulty.…”
mentioning
confidence: 99%